Quantitative Uniqueness for Mean Curvature Flow (Journal of Mathematical Study, 2025)
We show that by applying a set of existing analytical arguments, a more robust effective uniqueness result for blowups can be obtained, with multiple implications following therefrom.
Keywords: Uniqueness of blow ups; mean curvature flow; monotonicity